TGF-β1 Increases GDNF Production by Upregulating the Expression of GDNF and Furin in Human Granulosa-Lutein Cells - Yin, Jingwen (Cells, 2020)
Glial cell line-derived neurotrophic factor (GDNF) is expressed at a high level in the human ovary and GDNF signaling is involved in the direct control of follicular activation and oocyte maturation. Transforming growth factor-β1 (TGF-β1) plays an important role in the regulation of various ovarian functions. Furin is an intracellular serine endopeptidase of the subtilisin family that is closely associated with the activation of multiple protein precursors. Despite the important roles of GDNF and TGF-β1 in the regulation of follicular development, whether TGF-β is able to regulate the expression and production of GDNF in human granulosa cells remains to be determined. The aim of this study was to investigate the effect of TGF-β1 on the production of GDNF and its underlying mechanisms in human granulosa-lutein (hGL) cells. We used two types of hGL cells (primary hGL cells and an established immortalized hGL cell line, SVOG cells) as study models. Our results show that TGF-β1 significantly induced the expression of GDNF and furin, which, in turn, increased the production of mature GDNF. Using a dual inhibition approach combining RNA interference and kinase inhibitors against cell signaling components, we showed that the TβRII type II receptor and ALK5 type I receptor are the principal receptors that mediated TGF-β1-induced cellular activity in hGL cells. Additionally, Sma- and Mad-related protein (SMAD)3 and SMAD4 are the downstream signaling transducers that mediate the biological response induced by TGF-β1. Furthermore, furin is the main proprotein convertase that induces the production of GDNF. These findings provide additional regulatory mechanisms by which an intrafollicular factor influences the production of another growth factor through a paracrine or autocrine interaction in hGL cells.